Exploration of the Dual-Tutor Mechanism for Graduation Theses in Physics Major - Shi, Chuan; Chen, Xiaoyu (Asia Pacific Economic and Management Review, 2025)
Against the backdrop of collaborative talent cultivation and the new college entrance examination reform, the graduation theses of physics normal university students face problems such as the disconnection between theory and practice, and the insufficient connection between students' research capabilities and teaching practice abilities. Combining the interview practice of the dual-tutor mechanism at Tianjiabing Middle School in Ya'an, and taking the Department of Physics of Sichuan Minzu College as an example, this paper analyzes the connotation and value of the dual-tutor mechanism for graduation theses in physics major, sorts out the practical dilemmas such as the low willingness of high school teachers to participate and the difficulty in coordinating tutors' opinions, and proposes optimized paths including hierarchical incentives and collaborative communication. It provides a reference for the talent cultivation of physics major and the coordinated development of basic education.